Building Organisational Network Value - Barczak, Beata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Participation in a network and the ability to effectively use information and knowledge is a source of value. Taking this assumption as its starting point, the article presents the problem of creating value in organisational networks. It discusses the concept of value from the point of view of network efficiency, and the mechanisms and factors of value creation in organisational networks. It also looks at the problem of synergies in organisational networks and the importance of knowledge management processes and learning for value creation networks.